The soil temperature effect on carbon dioxide emissions in crops of various agricultural plants and fallows - Demin Evgeny; Miller Elena; Shakhova Olga; Akhtyamova Anastasia; Gaizatullin Andrey (BIO Web of Conferences)
The world’s population is currently facing a large number of problems that need to be resolved as soon as possible. One of these problems is climate change, which is associated with an increase in the concentration of greenhouse gases in the upper atmosphere. Agricultural production has a significant impact on the climate due to the high emissions of nitrous oxide and carbon dioxide from the surface of arable soils. The purpuse of the study is to evaluate the effect of cultivated crops, fallows and soil temperature on the rate of carbon dioxide emissions. The soil temperature under crops and fallows from May to July gradually increases from 8.9-10.1 to 19.2-21.8 °C, then drops to 6.9-7.3 °C. In spring wheat crops, the soil temperature until the middle of the growing season is 0.2-2.2 °C higher than in alfalfa and corn crops and 0.3-1.3 °C lower than in nacked steam. The rate of carbon dioxide emissions significantly depends on the type of crops being cultivated. At the beginning of the growing season, CO2 emissions range from 37.4 to 64.9 kg/ha, with the maximum observed in alfalfa crops and the minimum in spring wheat. In the dead fallow, the values during this period do not exceed 34.0 kg/ha. An increase in soil temperature led to an increase in the emission rate under crops to 93.2-121.0 kg/ha. The highest rate of CO2 production per day was observed in alfalfa crops, the minimum in spring wheat crops, and in dead fallow the values were at the level of 80 kg/ha. A decrease in the rate of soil respiration began to occur simultaneously with the cooling period of the soil and correlated well (r=0.85-0.94). The equations developed during the work indicated that, with a high probability (72-89%), a change in soil temperature by a degree Celsius changes daily emissions in the range of ±5.0 kg/ha for wheat fields; ±7.0 kg/ha for corn; ±7.4 kg/ha for alfalfa and about ±3.9 kg/ha for dead fallow. The share of crop effect in the carbon dioxide emission rate is 24.8%, while soil temperature is 67.3%.